Based on Network Pharmacology Tools to Investigate the Mechanism of Tripterygium wilfordii Against IgA Nephropathy - Xia, Ming; Liu, Di; Liu, Haiyang; Zhao, Juanyong; Tang, Chengyuan; Chen, Guochun; Liu, Yu; Liu, Hong (Frontiers in Medicine, 2021)
Background: IgA nephropathy (IgAN) is the most common primary glomerular disease and poses a global major public health burden. The preparation of Tripterygium wilfordii Hook F (TwHF) is widely applied for treating patients with IgAN in China, while the molecular mechanisms remain unclear. This study aimed to verify the therapeutic mechanism of TwHF on IgAN by undertaking a holistic network pharmacology strategy in combination with in vitro and in vivo experiments. Methods: TwHF active ingredients and their targets were obtained via the Traditional Chinese Medicine Systems Pharmacology Database. The collection of IgAN-related target genes were collected from GeneCards and OMIM. TwHF-IgAN common targets were integrated and visualized by Cytoscape. Gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analyses were performed to determine the predominant molecular mechanisms and pathways of TwHF on the treatment of IgAN. The protein-protein interaction network was constructed by the STRING online search tool, and hub genes were identified using R software. The expression of hub gene and related signaling were evaluated in TwHF-treated mice through immunohistochemistry and western blot and further validate in human mesangial cells (HMCs). In addition, Cell counting kit 8 (CCK8) and flow cytometry were used to detect the effects of TwHF on cell proliferation and cell cycle of mesangial cells. Results: 51 active ingredients were screened from TwHF and 61 overlapping targets related to IgAN were considered potential therapeutic targets, GO functions and KEGG analyses demonstrated that these genes were primarily associated with DNA-binding transcription factor binding, lipid, and atherosclerosis pathway. Genes with higher degrees including AKT1, CXCL8, MMP9, PTGS2, CASP3, JUN are hub genes of TwHF against IgAN. Verification of hub gene JUN both in vitro and in vivo showed that TwHF significantly attenuated JUN phosphorylation in the kidneys of IgAN mice and aIgA1-activated HMCs, meanwhile suppressed HMCs proliferation and arrested G1-S cell cycle progression. Conclusion: Our research strengthens the mechanisms of TwHF in treating IgAN, inhibition of JUN activation may play a pivotal role in TwHF in alleviating IgAN renal injury.